Rock in Roça: Pocket Show Rock in Roça - Vieira, Eduardo Atanázio; Pereira, Daniel Siqueira; Ribeiro, Breno Rattes Vilela; Paes, Márcio Renan Barreto Baptista; Souza, Maysa Abreu; Macedo, Vitória Aparecida Cruz Carvalho; Oliveira, Thalita Fortunato; Rangel, Estella Silveira Moreira; de Aguiar, Daniel da Silva Rezende (Encontro de Cultura do IFFluminense, 2021)
Pequena apresentação com execução de músicas ensaidas pela banda.